2020
DOI: 10.5194/soil-6-549-2020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of water and tillage erosion from <sup>239+240</sup>Pu tracer measurements using inverse modelling

Abstract: Abstract. Soil redistribution on arable land is a major threat for a sustainable use of soil resources. The majority of soil redistribution studies focus on water erosion, while wind and tillage erosion also induce pronounced redistribution of soil materials. Tillage erosion especially is understudied, as it does not lead to visible off-site damages. The analysis of on-site/in-field soil redistribution is mostly based on tracer studies, where radionuclide tracers (e.g. 137Cs, 239+240Pu) from nuclear weapon tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 68 publications
2
38
0
Order By: Relevance
“…4.2 ha) in the centre of our study area using 239 + 240 Pu and an inverse modeling analysis. The results showed that soil erosion by water is an order of magnitude lower compared to tillage erosion (Wilken et al, 2020) and, thus, support our findings that tillage erosion and the corresponding patterns in soil properties and plant growth conditions are dominant in this region. It is important to note that in our study, EVI is only a proxy for crop biomass.…”
Section: Methodological Considerationssupporting
confidence: 89%
See 4 more Smart Citations
“…4.2 ha) in the centre of our study area using 239 + 240 Pu and an inverse modeling analysis. The results showed that soil erosion by water is an order of magnitude lower compared to tillage erosion (Wilken et al, 2020) and, thus, support our findings that tillage erosion and the corresponding patterns in soil properties and plant growth conditions are dominant in this region. It is important to note that in our study, EVI is only a proxy for crop biomass.…”
Section: Methodological Considerationssupporting
confidence: 89%
“…We can safely assume that most of the erosion-related pattern of EVI was not caused by recent erosion (e.g., due to water losses by runoff) but related to long-term soil truncation and colluviation, which modify important soil properties influencing plant growth and crop biomass (e.g., rooting depth, bulk density, water and nutrient availability, etc.). Nevertheless, the modeled erosion patterns served well as proxy variables for long-term soil truncation or colluviation even though they were based on recent data of soil use valid for the last 60 years (Wilken et al, 2020). Most changes in erosion parameters like rain erosivity, cropping sequence, or tillage intensity, which might have happened, would not change the soil redistribution pattern but only the absolute amount.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations